مواقع التواصل الاجتماعیة الأکادیمیة - ایمان على سعد; د. خالد عبد الفتاح محمد Mohamed; د. اسماعیل رجب غریب Ghareeb (المجلة الدولية لعلوم المكتبات والمعلومات)
The research deals with the definition of social networking sites foracademic purposes, the date of their launch, the intellectual production ofacademic communication sites, the need to use them, the dangers of using them,and the exclusion of the most popular social networking sites.(1) Research Gate, founded in 2008 in Berlin by Ijad Madisch, HorstFickenscher, and Sören Hofmayer, (2) the site of Academia.edu, which wasfounded in 2008 in San Francisco by Richard Price, (3) Mendeley, founded in2007 by three German doctoral students; and (4) the Zotero site, launched in2006.The study pointed out that it is advantageous to use social networkingsites for academics Such as: sharing and discovering sources, supportingcooperation, developing identity and self, and communication.The risk of using it to researchers: wasting time, lack of enough activeusers, inefficient use, and lack of digital identity management.The risk of using it on institutions: the spread of knowledge that can beused badly by competitors, and lack of control over the reputation of institutions.Finally, the study pointed to the existence of two views on the relationshipbetween the use of social networking sites and academic achievement: The firstpoint of view: confirms that the relationship is negative between social networkingsites and academic achievement, and the second view assumes a positiverelationship between them.